AN ANALYSIS OF COMMUNITY PARTICIPATION IN THE IMPLEMENTATION OF THE COMPLETE SYSTEMATIC LAND REGISTRATION PROGRAM (PTSL) IN BATU BARA REGENCY - Nala Septiliana; Siti Hazzah Nur. R; Adang Aldhila (Universitas Muhammadiyah Sumatera Utara, 2026)
The Complete Systematic Land Registration (PTSL) program is designed to provide legal certainty over land, yet its implementation in Batu Bara Regency faces challenges regarding substantive community participation. This study aims to identify the forms and dynamics of community participation in each stage of PTSL. Using a descriptive qualitative method with data collected through in-depth interviews, passive participatory observation, and documentation, the study finds that community participation remains procedural and passive. Communities engage in submitting documents, attending socializations, and receiving certificates but are nearly absent from decision-making, monitoring, and evaluation. Enthusiasm for the program’s benefits (free, fast) is not matched by a deep understanding of post-certification rights and obligations. Referring to Arnstein’s Ladder of Participation, community participation is positioned at the informing and placation levels (tokenism), not yet reaching partnership. Main obstacles include limited access to information, low levels of understanding, and weak institutional coordination (e.g., between BPN and Bapenda). This study concludes that quantitative certificate achievements do not guarantee substantive participation. Community empowerment strategies and a transformation of power relations are necessary for PTSL to truly realize equitable legal certainty.